Pathways to Nursing and Midwifery Education in Tanzania with Reflection to the Global Perspectives: A Narrative Review. - Mwansisya, Tumbwene Elieza; Lyimo, Mary Apolinary; Pallangyo, Eunice Siaity (Nursing Reports, 2025)
Background/Objectives: This review aimed to explore the pathways of nursing and midwifery education in Tanzania and compare them with global perspectives. The goal was to identify similarities, differences, and areas for potential improvement to align with international standards. Methods: A narrative literature review was carried out through databases with published studies in nursing and gray literature. The database search included Medline, PubMed, Google Scholar, EBSCO, PsycINFO, clinical nursing, and gray literature from January 2014 up to December 2024. The search process was carried out by the authors with the following key words: admission, pathway to nursing profession, delivery mode, generative dynamic, and learning models. The search strategy included studies from selected countries in East Africa, Europe, North America, Australia, and Asia. The inclusion criteria were (1) published papers or reviews addressing the review topics; (2) studies published in the English language; (3) gray literature on the reviewed topics; (4) studies originating from Tanzania, East Africa, Europe, Asia, Australia, and North America. The selected countries served as a source for comparison of nursing and midwifery education in Tanzania with the globe. Results: A total of 758 articles were reviewed from the selected databases. Finally, 27 studies and 11 gray literature sources were included. In Tanzania, the overall duration of nursing education from primary education to a bachelor's degree for diploma graduates is relatively long. Students complete approximately 14 years of schooling from primary education to the completion of a diploma, including three years at the diploma level. To enroll in a degree program, candidates are required to have two years of professional experience, followed by four years of academic training and a mandatory one-year internship. Globally, the duration of educational programs is generally decreasing due to generational shifts and advancements in technology. Conclusions: Whilst nursing and midwifery education is regulated in Tanzania, the current admission criteria and duration of the program do not align with the global standards. Future studies that provide the comparison of curriculums among universities in Tanzania with global standards would provide a deep understanding of the competencies, teaching models, learning environment, duration, and desired learning outcomes for nursing and midwifery education.